Lawyers, conflict and transition - McEvoy, Kieran (UK Data Service, 2020)
The research for the Lawyers, Conflict and Transition project involved the completion of a project bibliography and an academic and policy literature review. It also included the conduct of approximately 120 confidential semi-structured qualitative interviews in Cambodia, Chile, Israel, Palestine, Tunisia and South Africa. The rationale which informed the final choice of jurisdictions were as follows. To study: a) Countries with a history of violence and/or oppression at different stages of transition b) Jurisdictions from the principal ‘legal families’ (Glenn 2006) i.e. the Common Law tradition, the Civil Law Tradition, Islamic tradition – and we would add Asian and African legal traditions c) Transitions in Middle Eastern countries, in part because of awareness that this region has been (relatively) overlooked to date and also because of the recent events known as the ‘Arab Spring’ d) Countries where it is possible to explore relevant theoretical issues including legal pluralism, post-colonial lawyering, understandings of the ‘rule of law’, cause-lawyering and legal culture e) Sites where the researchers have well established contacts and have identified local researchers f) Locations where fieldwork could be conducted safely Interviewees included national and international lawyers, political actors, victims' representatives, academics, judicial figures and NGO activists. Despite the centrality of the rule of law to the contemporary theory and practice of transitional justice, there is little emphasis in the relevant literature on the role of lawyers outside the courts or indeed as the 'real people' at work in the system. A core aim of the qualitative research was thus to explore in detail the role of individual lawyers in transitions from violence or authoritarianism. The project will explore the role of lawyers in transitions from violence or authoritarianism in Israel/Palestine, Cambodia, Chile, South Africa and Tunisia. The research will construct a bridgehead between transitional justice and the sociology of the legal professions. It will also draw upon a range of interdisciplinary literature, including comparative legal studies, historical institutionalism and social movement theory. The aims of the project are: to develop a comparative perspective on the sociology of lawyering exploring lawyers as actors within and beyond the courtroom; to examine the intersection between lawyers and other key civil society, political and legal actors in social movements to explore the contribution of lawyers in shaping local and international understandings of the ‘rule of law’ to interrogate the extent to which transitional contexts may be viewed as ‘exceptional’ from the experiences of settled democracies to chart the relevance (or not) of key themes on the relationship between law, lawyers and political and social change in such contexts, in particular legal culture, colonial and post-colonial lawyering and legal pluralism. The project will draw from comparative legal methods and socio-legal traditions of empirical fieldwork in conducting 120 semi-structured interviews across the six field sites.